Revealing novel quantum phases in quantum antiferromagnets on random lattices - Yu, R.; Haas, S.; Roscilde, T. (Condensed Matter Physics, 2009)
Quantum magnets represent an ideal playground for the controlled realization of novel quantum phases and of
quantum phase transitions. The Hamiltonian of the system can be indeed manipulated by applying a magnetic
field or pressure on the sample. When doping the system with non-magnetic impurities, novel inhomogeneous
phases emerge from the interplay between geometric randomness and quantum fluctuations. In this paper
we review our recent work on quantum phase transitions and novel quantum phases realized in disordered
quantum magnets. The system inhomogeneity is found to strongly affect phase transitions by changing their
universality class, giving the transition a novel, quantum percolative nature. Such transitions connect conventionally
ordered phases to unconventional, quantum disordered ones quantum Grif ths phases, magnetic
Bose glass phases exhibiting gapless spectra associated with low-energy localized excitations. Квантовi магнетики є iдеальним майданчиком для контрольованої реалiзацiї нових квантових фаз i квантових фазових переходiв. З гамiльтонiаном системи можна справдi манiпулювати, прикладаючи магнiтне поле або тиск до зразка. Коли допувати систему немагнiтними домiшками, з’являються новi неоднорiднi фази через конкуренцiю мiж геометричною випадковiстю i квантовими флуктуацiями. У цiй статтi ми робимо огляд нашої недавньої працi з квантових фазових переходiв i нових квантових фаз, якi реалiзуються у невпорядкованих квантових магнетиках. Виявлено, що неоднорiднiсть системи сильно впливає на фазовi переходи, змiнюючи їх клас унiверсальностi, i приводить до нової квантово-перколяцiйної природи переходу. Такi переходи пов’язують звичайнi впорядкованi фази з незвичайними квантовими невпорядкованими фазами – квантовими фазами Грiфiтса, фазами магнiтного бозе-скла, якi мають безщiлинний спектр, зв’язаний з низькоенергетичними локалiзованими збудженнями.